2019
DOI: 10.1139/apnm-2018-0354
|View full text |Cite
|
Sign up to set email alerts
|

Improving hepatic mitochondrial biogenesis as a postulated mechanism for the antidiabetic effect ofSpirulina platensisin comparison with metformin

Abstract: Various nutritional and medicinal potencies have been accredited to metabolites from the cyanobacteria, Spirulina platensis (Arthrospira platensis) sp. Hence, our study was designed to examine whether the Spirulina supplementation would possess beneficial effects in type 2 diabetes mellitus (T2DM), in comparison with metformin. High fat diet/low dose streptozotocin (HFD/STZ) model was adopted and the diabetic rats were orally treated with metformin (200 mg/kg) or Spirulina (250 or 500 or 750 mg/kg) for 30 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…S. platensis has been reported recently to exhibit antihyperglycaemic effects, but the mechanism of action was not elucidated (23)(24)(25) . This study has examined the insulinotropic effects of S. platensis using the perfused rat pancreas, isolated mouse islets and the clonal BRIN-BD11 β-cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. platensis has been reported recently to exhibit antihyperglycaemic effects, but the mechanism of action was not elucidated (23)(24)(25) . This study has examined the insulinotropic effects of S. platensis using the perfused rat pancreas, isolated mouse islets and the clonal BRIN-BD11 β-cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Active constituents exhibit anti-inflammatory, neuroprotective, hepatoprotective, immunomodulatory and anticancer activities (22) . A recent animal study reported potential anti-diabetic effects of S. platensis, but the mechanisms underlying such effects are unknown (23)(24)(25) . In this paper, we have made a detailed study of effects of S. platensis on pancreatic insulin release, dipeptidyl peptidase IV (DPP-IV) inhibition and various gastrointestinal (GI) tract actions to elucidate the mechanism and therapeutic potential of S. platensis for improvement of diabetes control.…”
mentioning
confidence: 99%
“…In addition to microbial signals, there is the possibility that food components themselves influence mitochondrial function. Rat models (post-weaned, adult animals) indicate that mitochondrial function of liver and skeletal muscle can be modulated by dietary components [13,[46][47][48][49][50][51]. However, nothing is known about the effect of postnatal diet on mitochondrial function, especially in the splanchnic tissues that would be exposed to dietary components and microbialderived factors that might regulate metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A. platensis (5% in the diet) counteracted renal injury and oxidative stress in alloxan-induced diabetic rats [29]. A. platensis also showed antidiabetic effects in streptozotocin (STZ)-injected rats [30][31][32]; animals injected with STZ are also models of T1DM [28]. A. platensis (500 mg/kg body weight, 2 months) significantly decreased serum glucose, HbA1c, and malondialdehyde (MDA) levels and significantly increased the serum insulin concentration and the activity of antioxidant enzymes, as well as normalizing their mRNA gene expression and inducing upregulation of the gluconeogenic enzyme pyruvate carboxylase (PC), the pro-apoptotic factor Bax and caspase-3 (CASP-3), and TNF-α gene expression [31].…”
Section: Spirulina (Arthrospira) and Metabolic Alterationsmentioning
confidence: 99%
“…The authors suggested that the antioxidant, anti-inflammatory, and anti-apoptotic properties of spirulina might be due to its polyphenolic components. In an HF diet/low-dose STZ (HFD/STZ) rat model of diabetes, oral doses of A. platensis (250, 500 or 750 mg/kg body weight) for 30 days were shown to ameliorate levels of fasting blood glucose, insulin, and hepatic enzymes [32]. A. platensis also influenced the serum lipid profile and exhibited an anti-inflammatory effect via TNF-α and adiponectin modulation, in turn, probably mediated by the sterol regulatory element-binding transcription factor-1c (SREBP-1c) [32].…”
Section: Spirulina (Arthrospira) and Metabolic Alterationsmentioning
confidence: 99%